AMSS Third Regional Conference: Arlington, TX - August 23, 2003 (American Journal of Islam and Society, 2003)
At its Third Regional Conference, the AMSS broke new ground, dispellingthe popular image that Muslims are extremists and Islam isengaged in holy war against the West. Mayor Robert Cluck welcomed theparticipants, praised American Muslim organizations' condemnation of9/11, and thanked AMSS for informing Americans about Islam and theMuslim contribution to civilization through its publications and annualconventions. MSA president Laith Albataineh welcomed the participantson behalf of the students.In his introduction, Chairman Basheer Ahmed stated that extremismand terrorism were not unique to a single religion. He exhorted all peacelovingpeople to unite to rein in extremism before it gets out of control.Congressman Martin Frost (D-Texas), the guest of honor at the luncheon,referred to his post-9/11 statement encouraging every Texan to join him inresisting intolerance and bigotry. While condemning terrorism in theMiddle East, he expressed his support for the "roadmap to peace" and aPalestinian state. Congressman Frost is known for his support of civilrights, getting more immigrants into the American armed forces, constituent service, upholding the Bill of Rights, furthering his district's economic development, and assisting students' career development.Moazam Syed, American Muslim Alliance president elect (TarrantCounty) thanked the congressman; said that terror, hatred, and prejudice arealien to all religions; and that: "America will remain just and tolerant, evenwhen confronted with terror and adversity." Bob Ray Sanders, Star Telegramstaff writer and columnist, moderated the question and-answer session.Jamal Badawi (Saint Mary's University, Halifax, Canada) dispelled theinaccurate notions that the Arabic words for "holy war'' can be found in theQur' an, that kufr means "infidel," that Allah is the God of Muslims only, thatIslam is exclusivistic, and that an unbeliever (kafir) does not have the sameright to life as a Muslim, and several other often-misunderstood notions. Heaffirmed that practice or juristic opinions could not replace the Qur'an andahadith, advocated an integrative contextual approach toward understandingthese texts, and pointed out common pitfalls in their interpretation. Hisstatements were well-received by both Muslims and non-Muslims.AMSS president Louay Safi analyzed the present extremism found inthe Muslim world as being based on distorted interpretations of scripture ...